2010
DOI: 10.1002/adfm.201000071
|View full text |Cite|
|
Sign up to set email alerts
|

Low‐Temperature Superionic Conductivity in Strained Yttria‐Stabilized Zirconia

Abstract: We report very high lateral ionic conductivities in epitaxial cubic yttria-stabilized zirconia synthesized on single crystal SrTiO 3 and MgO substrates by reactive direct current magnetron sputtering. Superionic conductivities (i.e., ionic conductivities of the order ~1 Ω -1 cm -1 ) are observed at 500 ºC for 58-nm-thick films on MgO. Our results indicate a superposition of two parallel contributions -one due to bulk and one attributable to the film-substrate interface.Interfacial effects dominate the conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
115
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 31 publications
4
115
2
1
Order By: Relevance
“…In general, literature data are quite consistent concerning the increased oxygen-ion conductivity of interfaces showing a large dislocation density, 4,7,9 but whether the interfacial strain can play a significant role in enhancing the ionic conductivity is still quite a controversial issue.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In general, literature data are quite consistent concerning the increased oxygen-ion conductivity of interfaces showing a large dislocation density, 4,7,9 but whether the interfacial strain can play a significant role in enhancing the ionic conductivity is still quite a controversial issue.…”
mentioning
confidence: 92%
“…6,9 However, STO is not a good insulator at high temperatures, and conductivity measurements of thin films deposited on STO might be significantly affected by the substrate. 11 (100) and (110) MgO substrates, for which the insulating properties at high temperatures are well demonstrated, have been used for the fabrication of grain-boundary-free ultra-thin 8.7 mol% yttriastabilized zirconia (8.7YSZ 1 ) layers.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Looking at the SOFC system perspective it is insufficient only to improve a single cell component in order to drastically increase the cell performance as it has been shown that all cell components (cathode, electrolyte, and anode) contribute with considerable losses in the SOFC. [10] Therefore, work on novel cathode materials is highly important.…”
Section: Introductionmentioning
confidence: 99%
“…Because of what is known in metals, dislocations have been therefore suggested to enhance ionic conductivity in oxides as well [28][29][30] . For example, Sillassen et al 28 have observed 3.5 orders of magnitude acceleration in the ionic conductivity for a 8.7 mol.% yttria-stabilized zirconia (YSZ) epitaxial film on MgO substrate. They attributed this enhancement qualitatively to a combination of misfit dislocations and elastic strain at the interface.…”
mentioning
confidence: 99%